Review article: defining remission in ulcerative colitis. - Travis, S; Higgins, P; Orchard, T; Van Der Woude, C; Panaccione, R; Bitton, A; O'Morain, C; Panés, J; Sturm, A; Reinisch, W; Kamm, M; D'Haens, G (2011)
BACKGROUND: There is no international agreement on scoring systems used to measure disease activity in ulcerative colitis, nor is there a validated definition for disease remission. AIM: To review the principles and components for defining remission in ulcerative colitis and propose a definition that will help improve patient outcomes. METHODS: A review of current standards of remission from the perspective of clinical trials, guidelines, clinical practice and patients was conducted by the authors. Selected literature focused on the components of a definition of remission, the utility of a definition and treatment strategies, based on current definitions. RESULTS: Different definitions of remission affect the assessment of outcome and make it difficult to compare trials. In the clinic, endoscopy is rarely used to confirm remission, because mucosal healing has only recently begun to be related to the duration of subsequent remission in a way that will affect clinical practice. Histopathology may be the ultimate arbiter of mucosal healing. There is no agreement on the definition of remission in current guidelines. Patient-defined remission may predict endoscopic remission, but has yet to be shown to predict duration of remission. CONCLUSIONS: A standard based on clinical symptoms and endoscopy is proposed. Histopathology is a third dimension of remission that may have prognostic value. The definition of remission should help predict long-term outcome. The expectations of patients and their physicians need to be raised, as the goal of treatment of active ulcerative colitis should be to induce remission.